The prognostic role of circulating tumor cells in colorectal cancer. Issue 12 (2nd December 2019) - Nanduri, Lahiri Kanth; Hissa, Barbara; Weitz, Jürgen; Schölch, Sebastian; Bork, Ulrich
ABSTRACT: Introduction : Metastasis is the main cause of cancer-associated death in colorectal cancer (CRC). The presence of circulating tumor cells (CTC) in the blood is associated with an increased risk of recurrence and poor prognosis. The clinical significance of CTCs as a novel biomarker has been extensively studied in the last decade. It has been shown that CTC detection applies to early cancer detection. The presence of CTCs is associated with metastatic spread and poor survival and is also useful as a marker for therapy response. Areas covered : We summarize the role of CTC in CRC, their clinical significance, current methods for CTC detection and challenges as well as future perspectives of CTC research. Expert commentary : The clinical significance of CTC in CRC patients is well established. Although insightful, the available marker-based approaches hampered our understanding of the CTCs and their biology, as such approaches do not take into account the heterogeneity of these cell populations. New technologies should expand the marker-based detection to multi biomarker-based approaches together with recent technological advances in microfluidics for single cell enrichment and analysis.